N.I. VAVILOV’S TRIP IN THE USA AND WESTERN EUROPE IN 1921–1922 - T. B. Avrutskaya (Вавиловский журнал генетики и селекции)
The first visit of NI Vavilov to the United States in 1921 is the least studied period of the scientist’s life. The documents and photographs first published in this paper provide a more detailed view of this trip, its objectives and results.